Tuberculosis-associated obstructive pulmonary disease: a clinical, radiological and pathophysiological study of the contribution of previous pulmonary tuberculosis in a community-based study of chronic obstructive pulmonary disease - Allwood, Brian William (Department of Medicine, 2015)
Includes bibliographical references.